Manajemen Risiko Pembiayaan Murabahah Sertifikasi Guru di Bank Syariah - Bella, Yunnafa Salsa (JIOSE: Journal of Indonesian Sharia Economics, 2023)
This study aims to determine the risks that arise in murabahah financing for teacher certification (sergu) and to find out how the risk management for murabahah teacher certification (sergu) is in Islamic banks. The object of this research is PT. BPR Syariah Artha Mas Abadi Waturoyo Margoyoso Pati. This study uses a descriptive qualitative research method with data obtained from observations, interviews, and documentation. The results of this study indicate that in murabahah financing for teacher certification (sergu) there are several risks that may occur, namely the risk of duplicating educator certificates by customers, delays in disbursing certification funds by the government, customers or teachers who make financing being fired from their jobs while the financing process is still ongoing, and customer certification funds are revoked by the government. This research shows that PT. BPR Syariah Artha Mas Abadi implements risk management for murabahah financing for teacher certification (sergu) that is good and in accordance with the provisions, consisting of risk identification, risk measurement, risk monitoring, and risk control.